2021
DOI: 10.3389/fendo.2021.725559
|View full text |Cite
|
Sign up to set email alerts
|

Crash Landing of Thyroid Storm: A Case Report and Review of the Role of Extra-Corporeal Systems

Abstract: Thyroid storm is a rare but life-threatening endocrinological emergency with significant mortality ranging from 10-30% with multi-organ involvement and failure. In view of the rarity of this condition and efficacy of established first line medical treatment, use of extra-corporeal treatments are uncommon, not well-studied, and its available evidence exists only from case reports and case series. We describe a 28-year-old man who presented with an out-of-hospital cardiac arrest secondary to thyroid storm. Despi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 47 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…[7,8] In addition, it has been reported to successfully used in hyperthyroid patients with antithyroid drug-induced hepatotoxicity. [3,5] Several mechanisms may as followings [5,9] : (1) TPE can clear protein-bound thyroid hormones while nearly 99% of the circulating thyroid hormones are bound to serum proteins; (2) TPE can bring new binding sites for free thyroid hormone from replacement with Alb solution to further reduce FT3 and FT4 levels; (3) TPE is also effective to reduce TRAB levels. A decrease in TRAb should play a role in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…[7,8] In addition, it has been reported to successfully used in hyperthyroid patients with antithyroid drug-induced hepatotoxicity. [3,5] Several mechanisms may as followings [5,9] : (1) TPE can clear protein-bound thyroid hormones while nearly 99% of the circulating thyroid hormones are bound to serum proteins; (2) TPE can bring new binding sites for free thyroid hormone from replacement with Alb solution to further reduce FT3 and FT4 levels; (3) TPE is also effective to reduce TRAB levels. A decrease in TRAb should play a role in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…The patient had no personal history of thyroid disease, but he was at a serious risk of severe heart failure due to atrial fibrillation and high ventricular frequency, in spite of the multiple pharmacological treatments failing to promptly restore a euthyroid status. In the literature, few similar cases described the application of TPE in patients with AIT, cardiac failure, or dangerous arrhythmias [ 3 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic process is difficult due to the absence of defined clinical and biochemical criteria. It is essential to recognize this condition early to ensure prompt therapy and provide specific management, if necessary [ 3 ]. In cases of underlying conditions or frailty conditions, such as heart failure or atrial fibrillation, a thyroid storm can precipitate the clinical course to MOF.…”
Section: Introductionmentioning
confidence: 99%
“…[29] For patients who cannot tolerate drugs or have failed drug therapy, alternative treatments need to be considered, including the use of extracorporeal systems such as continuous renal replacement therapy (CRRT), veno-arterial extracorporeal membrane oxygenation (VA-ECMO), and therapeutic plasma exchange (TPE), etc. [12] The recommended doses of glucocorticoids in this condition are hydrocortisone 100 mg every 6–8 h (300–400 mg/d) or dexamethasone 2 mg intravenous injection every 6 h (8 mg/d) continued until the resolution of the TS. [30] However, a recent large-scale data analysis found that routine use of corticosteroids did not improve survival in patients with TS.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] According to a Japanese survey, the annual incidence of thyroid storm in hospitalized patients is 0.2/100,000, and the mortality is 10%-30%, with a 12-fold increase in mortality compared to individuals with thyrotoxicosis. [2,3,12,13] Hyperthyroidism is associated with a variety of neurological diseases, such as chronic hyperthyroid myopathy, hyperthyroid hypokalemic periodic paralysis, and hyperthyroid myasthenia gravis. However, it is relatively rare to combine ischemic cerebrovascular diseases, such as cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%